The effects of consanguineous marriage on small kidney in chronic kidney disease (Annals of Medical Research, 2023)
Aim: To determine the effects of small kidney and consanguineous marriage in chronic kidney disease (CKD).Materials and Methods: Patients with a vertical kidney size of 100 mm or less, who applied to the outpatient clinic between September 2021 and 2022, were included in the study. Urinary ultrasonography and renal function tests were recorded one year apart. Two groups, with and without relatives, were compared. SPSS 22.0 program was used for statistics. P< .05 was considered significant.Results: The parents of 50 of the 94 cases with small kidney included in the study were related and 44 of them were not related. 57.4% were female, mean age was 49.86. Urea, creatinine, e-GFR, hemoglobin, albumin, phosphorus, calcium, PTH, ferritin and urinary USG used in chronic kidney disease progression follow-up were compared between the groups with and without parental consanguinity.Conclusion: Early application of prevention measures with ultrasound detection of small kidney related to consanguineous marriage at an earlier age in before kidney dysfunction is established will slow down the progression.
Keywords: Small kidney; Chronic kidney disease; Progression